Perimetric visual field and functional MRI correlation: implications for image-guided surgery in occipital brain tumours - Roux, F-E; Ibarrola, D; Lotterie, J-A; Chollet, F; Berry, I (Journal of neurology, neurosurgery and psychiatry, 2001)
OBJECTIVE To compare the results of visual functional MRI with those of perimetric evaluation in patients with visual field defects and retrochiasmastic tumours and in normal subjects without visual field defect. The potential clinical usefulness of visual functional MRI data during resective surgery was evaluated in patients with occipital lobe tumours. METHODS Eleven patients with various tumours and visual field defects and 12 normal subjects were studied by fMRI using bimonocular or monocular repetitive photic stimulation (8 Hz). The data obtained were analyzed with the statistical parametric maps software (p<10-8) and were compared with the results of Goldmann visual field perimetric evaluation. In patients with occipital brain tumours undergoing surgery, the functional data were registered in a frameless stereotactic device and the images fused into anatomical three standard planes and three dimensional reconstructions of the brain surface. RESULTS Two studies of patients were discarded, one because of head motion and the other because of badly followed instructions. On the remaining patients the functional activations found in the visual cortex were consistent with the results of perimetric evaluation in all but one of the patients and all the normal subjects although the results of fMRI were highly dependent on the choices of the analysis thresholds. Visual functional MRI image guided data were used in five patients with occipital brain tumours. No added postoperative functional field defect was detected. CONCLUSIONS There was a good correspondence between fMRI data and the results of perimetric evaluation although dependent on the analysis thresholds. Visual fMRI data registered into a frameless stereotactic device may be useful in surgical planning and tumour removal.